Purification and characterization of L-asparginase producing bacteria MNTG-7 - M. Sunitha (International Journal of Pharmacy and Analytical Research, 2015)
Several techniques have been described for recovery and purification of L-asparaginase from different sources. The present study was undertaken to recover and purify L-asparaginase from mutated MNTG-7 cell line using three-step procedure involving ammonium sulphate precipitation, ion exchange and gel filtration chromatography followed by the characterization of the purified enzyme. Protein molecular mass markers, DEAE cellulose and Sephadex G-200 matrices, Agarose, acrylamide, bis-acrylamide, sodium dodecyl sulfate (SDS), TEMED, ammonium persulphate and bovine serum albumin were used in the purification process.